1958
DOI: 10.1021/ja01536a052
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Alkyl Aryl Phosphates from Aryl Phosphorochloridates. I. The Sodium Alkoxide Route1

Abstract: 727acts similarly to ATP in regard to chelation with The infrared evidence indicates the P-0-P and ^Ilg++ as observed in infrared spectra. However, the purine nucleus are involved in the complex for-Szent-Gyorgyi concludes that chelation with mation with -1Ig++ and that the two former groups l l g t t is possible only with ATP and not with ADP, should be within the same molecule; however, it but the present results suggest that ATP and A4DP does not clearly demonstrate whether the complexform similar types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1965
1965
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Yields ranged from 0 to 45%. These results are in agreement with those of Orloff, Worrel, and Markley (8), who found that the yield of dichloridate was decreased by the presence of electronwithdrawing substituents in the aryl group. We have noted that traces of catalyst in the crude product appear to promote disproportionation at distillation temperatures.…”
Section: Ii!supporting
confidence: 93%
See 2 more Smart Citations
“…Yields ranged from 0 to 45%. These results are in agreement with those of Orloff, Worrel, and Markley (8), who found that the yield of dichloridate was decreased by the presence of electronwithdrawing substituents in the aryl group. We have noted that traces of catalyst in the crude product appear to promote disproportionation at distillation temperatures.…”
Section: Ii!supporting
confidence: 93%
“…Very little information outside the patent literature (7,5,9) is available on the esterification and amidation of aryl phosphorodichloridates. Orloff, Worrel, and Markley (8) prepared triesters by the solvolytic reaction of aryl phosphorodichloridates with alcohols.…”
Section: Ii!mentioning
confidence: 99%
See 1 more Smart Citation
“…All kinds of phosphorous acid dichloride were synthesized according to the literature procedures. [11][12][13] Solvents were dried prior to use when necessary with appropriate drying agents. Reactions were carried out in a flame-dried apparatus under the dry atmosphere of nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Scheme 3 2,6-Dimethoxyphenyl phosphorodichloridate 12 was prepared according to the procedure of Orloff et al 12 by the reaction of 11 with POCl 3 in the presence of AlCl 3 , and immediately used to prepare a diastereomeric mixture of 14 in 80 % yield by reaction with L-leucine methyl ester hydrochloride 13. Diastereomeric mixture of 14 was then converted into 15, as single diastereomer, in 57% yield by reaction with 6 in THF solution in the presence of imidazole at room temperature.…”
mentioning
confidence: 99%